Development of an applicattion to improve traceability and food safety management - Pinto, D. B. (2005)
Food safety has become an important food quality attribute within the last decade. Facing recent food scandals taken up by the media, consumers are more and more concerned about and interested in the provenance and authenticity of their food. Both food industry and authorities need to be able to trace back and to authenticate food products and raw materials used for food production to comply with legislation and to meet the food safety and food quality requirements as well as the increasing consumer demand. Therefore, food companies are faced with the problem of defining and implementing a series of procedures, controls and measures. Moreover, it is necessary to define an application method which is both rigorous and economically sustainable in order to guarantee the safe production of food and to be able to trace it along the food chain. The application was designed to manage traceability as well as to help in the quality control and production improvement, using an user-friendly interface. This application was developed in Visual Basic over an SQL database and its main features are: to register quality control parameters of raw materials, in-course products and final products; to manage reception, production and expedition orders; to analyse production costs, productivity, raw materials and products’ consumptions; to define and print labels containing lot information and other relevant data; to trace products during the food chain (from raw materials to final client). All these informations are accessible either from pre-defined reports either exported to intranet based on Internet Explorer or other browser. Usually the process to assure traceability, specially in food products (due to the large number of ingredients involved in a single formulation) is very time-consuming, involves lots of paperwork and consequently a large number of resources are expended in this laborious task. This application can minimize efforts involved in traceability and managing food quality and safety systems.